Online In-service Teacher Professional Development in Malaysia: A New Possibility? - Lim , Tina Swee Kim (2010)
Predominant forms of INSETT available have been known to be inflexible in terms of time and resources, not meet teachers’ actual needs, cause a loss of instructional time with students, and not incorporate sustained collaborative endeavors, nor offer further support after the program. In view of the increasing successful utilization of online in-service teacher professional development in complementing traditional forms of INSETT in other countries such as the USA, it is time that Malaysia seriously considers similar innovations. As such the purpose of this paper is among others, to examine (1) factors that would cause them to consider participating in online INSETT programs, (2) ICT self-efficacy, and (3) perceived value of various ICT tools for future professional development. Findings indicate that the in-service teachers sampled in this study were generally positive about online INSETT and appeared ready in terms of basic ICT competencies. (Authors' abstract)